Fourth-Semester Students’ Perception of Online Speaking Class: Participation and Interaction - Amaluddin; Syatriana, Eny; Hijrah (FKIP Unismuh Makassar, 2019)
This study aimed to discover students' perception of online speaking classes particularly about students' participation and classroom interaction using a qualitative descriptive method. The subjects of this study were fourth-semester students of the English Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. The study used interviews as an instrument to collect in this study.Based on the results of the study, student participation in taking online speaking classes is very high, this can be seen from the activeness of students in participating starting from a high level of attendance, preparing before entering class, being active in class discussions, contributing to group assignments, and being active in their abilities. improved communication. In addition, students have a positive perspective on class interactions. This can be proven by the existence of various types of interactions during this online speaking class.